Analysis of Factors Influencing Intention to Purchase Natural And Environmentally Friendly Cosmetic Products - Zaki Bahaiyan, Salim; Ridanasti, Erlita (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The popular trend in the global beauty industry has reshaped consumer consumption patterns, including in Indonesia. However, the unsustainable consumption of cosmetic products poses risks to environmental and social sustainability. With the phenomenal growth of the rapidly expanding cosmetic industry, the consumption of cosmetic products has also increased significantly. Unfortunately, this increase has negative environmental impacts and can harm consumer health. This is due to waste from raw materials used in production, product packaging, and chemicals that may pose health risks to consumers. Alternatively, green products have been widely developed and are available in the market. This study aims to examine the factors influencing the purchase intention of natural and eco-friendly cosmetic products among Indonesian consumers. To establish a hypothesis framework, 161 valid questionnaires were collected through purposive sampling in several cities in Indonesia. Data analysis and hypothesis testing were conducted using SmartPLS statistical software. The study results indicate that Indonesian consumers’ purchase intentions for natural and eco-friendly cosmetic products tend to be positively influenced by consumers’ attitudes toward environmental concern, health consciousness, and perceived behavioral control. Additionally, purchase intention positively impacts behavioral intention. These findings provide insights into Indonesian consumers' habits and awareness in choosing natural and eco-friendly cosmetic products.